2016
DOI: 10.18768/ijaedu.83563
|View full text |Cite
|
Sign up to set email alerts
|

Middle School Students’ Digital Game Experiences in the City of Makkah in Saudi Arabia

Abstract: The purpose of this quantitative study is to investigate middle school students" experiences with gaming in Makkah City in Saudi Arabia. This study described the current condition of video game usage and compared that depth of usage to current academic grade point average (GPA). Also, it showed the difference between gender, and students" age and described the types of video games and elements that attract students to play video games. There were 201 middle schools students from Makkah who participated in this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(16 citation statements)
references
References 2 publications
7
9
0
Order By: Relevance
“…These results were supported by references [3]- [24]. Although the difference between gender about the type of preferring games is no important for this study, this difference proves the agreement between this study and previous studies.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…These results were supported by references [3]- [24]. Although the difference between gender about the type of preferring games is no important for this study, this difference proves the agreement between this study and previous studies.…”
Section: Discussionsupporting
confidence: 92%
“…This result was expected and complemented the literature because many studies also found similar differences between male and female [2]- [3]- [14]- [27]- [32][35]- [37]. There are many reasons for these differences.…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…Video games are defined as games played through an electronic system such as a computer, console, or a digital phone. It represents a very popular leisure activity among children and adolescents in Arab countries and worldwide [1][2][3][4] and those games seem to have an influence on the behavior of adolescents [5] . Studies have shown that about 59-73% of youth were playing video games on any given day [6,7] .…”
Section: Introductionmentioning
confidence: 99%